The 2nd International Online-Conference on Nanomaterials 2020
DOI: 10.3390/iocn2020-07816
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Functionalization of Chitosan and Gelatin Type B Nanoparticles to Develop Novel Highly Biocompatible Cell-Penetrating Agents

Abstract: Nowadays, nanoparticles (NPs) are used to make safe and more effective biomedical technologies for applications in highly targeted therapeutics and drug-delivery vehicles. This helps avoid low cellular penetration and accumulation of the drug in intracellular endosomal compartments that are not of interest to a particular therapy. A way to enhance therapeutic efficiency is through nanoparticle loading systems. This study aims to develop low molecular weight (LMW) and high molecular weight (HMW) chitosan and ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Similar results were found for platelet aggregation, where the nanobioconjugates exhibited thrombogenic activities comparable to the negative control (PBS-1X), i.e., they remained at around 50% for concentrations up to 150 µg/mL. Similar hemocompatibility results were also reported by us recently for BUF-II-CNPs nanobioconjugates [74]. However, in a situation where the CNPs-AHB-1 nanobioconjugates were to be employed at concentrations above 300 µg/mL, they should be evaluated further, considering that they start to induce mild platelet activation at such concentration levels and, consequently, the possibility of thrombotic complications [75].…”
Section: Molecular Dynamics Simulationssupporting
confidence: 89%
“…Similar results were found for platelet aggregation, where the nanobioconjugates exhibited thrombogenic activities comparable to the negative control (PBS-1X), i.e., they remained at around 50% for concentrations up to 150 µg/mL. Similar hemocompatibility results were also reported by us recently for BUF-II-CNPs nanobioconjugates [74]. However, in a situation where the CNPs-AHB-1 nanobioconjugates were to be employed at concentrations above 300 µg/mL, they should be evaluated further, considering that they start to induce mild platelet activation at such concentration levels and, consequently, the possibility of thrombotic complications [75].…”
Section: Molecular Dynamics Simulationssupporting
confidence: 89%
“…In chitosan, the positively charged groups such as the amino groups result in net positive zeta potential. 33 , 34 …”
Section: Resultsmentioning
confidence: 99%
“…The carboxylic acid groups in gelatin cause a decrease in zeta potential. In chitosan, the positively charged groups such as the amino groups result in net positive zeta potential. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The outputs are in good agreement with DLS results. González et al [17] have shown the morphology of CS NPs through low molecular weight by TEM analysis that has the size of individual particles was 5 to 10 nm.…”
Section: Preparation and Characterization Of Npsmentioning
confidence: 99%